Negara, Masyarakat, dan Identitas (Studi Tentang Peraturan Wajib Berhijab di SMP N 3 Genteng) - Palufi, Nurwulan Intan; Erawan, I Ketut Putra; Noak, Piers Andreas (Jurnal Nawala Politika, 2023)
State, Society, and Identity (Study of mandatory hijab regulations at SMP N 3 Genteng) This research seeks to analyze the formation and implementation of regulations regarding the obligation to wear the hijab in one of the First State Schools in Banyuwangi, namely SMP N 3 Genteng, which requires all female students to wear the hijab, applies to both Muslims and non-Muslims as a whole. This study seeks to find out how the community and local government respond to these regulations. This study uses the theory of Bouendaries from Joel S. Migdal and uses the concept of the boundary between the state and society. Then from the results of the author's observations the formation of regulations was made by the school directly without agreement and without the knowledge of the local government or related ministries. The obligatory hijab regulation for all female students was rejected by the students' parents, this was because they were not Muslim. So that research can be supported by the theory of Bouendaries, which states that the state and society have limits on themselves and their respective groups. This regulation is a coercion against the use of the hijab for students who are not Muslim, by the school it is something that violates and has crossed the line for personal problems in society. By using in-depth interviews and observation research methods, it has been answered that these regulations have violated national boundaries within community groups, regarding personal issues, namely freedom to wear the hijab. Keywords: Regulations, Hijab, and Bouendaries.